Efektivitas Pelatihan Peer Educator Berbasis Masyarakat terhadap Pengetahuan dan Sikap dalam Upaya Pencegahan Perilaku Berisiko pada Masa Pandemi COVID-19 - Fitriani Mediastuti; Reni Tri Lestari (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Background: The pandemic COVID-19 has had an impact on various sectors. One of those affected is teenagers. During the pandemic, teenagers are unable to carry out activities such as school and extracurricular activities. This can affect risky behavior in adolescents if adolescents do not have the knowledge to prevent it. Community-based peer educator training during the pandemic COVID-19 is urgently needed by youth as agents of change. Health promotion by involving youth has a more effective impact.Objective: This study aims to determine the application of community-based peer educator training on an adolescent knowledge and an attitudes in preventing risky behavior during the pandemic.Methods: This research is a quasi-experimental research with one group pretest-posttest design. The research location is Village A, Ngaglik District, Sleman Regency. Respondents were selected by purposive sampling. Data analysis was carried out with a sample paired t test and using SPSS supporting software.Results: Statistically, the results showed that adolescents' knowledge after receiving the training material increased compared to before and had a significance (p-value=0.01). The attitude of adolescents after receiving the material increased compared to before and had a significance (p-value = 0.01).Conclusion: Training peer educator based on community during the pandemic was effective on adolescent knowledge and attitudes to prevent risk behavior.Recommendation: There needs to be a joint commitment (BKKBN, educational institutions through the PIKM forum and village government) so that training peer educator based on community is more optimal and sustainable.